silver (fox) (1970)
silver n The red fox is especially large and handsome. Its black or "silver" variety frequently commands a price of from one to five hundred dollars. They are taken chiefly in the north-east. PRINTED ITEM G.M.Story JUN 1970 JH JUN 1970 Used I and Sup Used I and Sup 2 Not used ~ fir/fox/hair (fox)/jar/thaw/ patch fox, GLITTER, PATCH FOX. The source is not listed in DNE.